Mastering Bitcoin: Programming the Open Blockchain - Antonopoulos, Andreas M (O'Reilly Media, Inc, 2024)
A broad introduction to Bitcoin and its underlying blockchain—ideal for nontechnical users, investors, and business executives. An explanation of Bitcoin's technical foundation and cryptographic currency for developers, engineers, and software and systems architects